ANALISIS PENGARUH PRICE, PROMOTION, PEOPLE DALAM STRATEGI PEMASARAN TERHADAP KINERJA PEMASARAN KREDIT KONSUMTIF PADA PT. BPR HASA MITRA MAKASSAR - I Made Semadi; Rustan DM; Fitriany Fitriany (Jurnal Aplikasi Manajemen & Kewirausahaan MASSARO, 2022)
This study aims to determine and analyze: the effect of price, promotion and people on the consumer credit marketing performance of PT BPR Hasa Mitra Makassar based on a quantitative approach with associative descriptive method. This research was conducted at PT BPR Hasa Mitra Makassar Main Branch Office with an allocation of two months from March to April 2022. The population of this study were all 51 (fifty-one) employees of PT BPR Hasa Mitra Main Branch Office and all population is used as the object of research. The results of the study indicate that: 1) There is a direct positive and significant effect between price on the marketing performance of consumer credit at PT BPR Hasa Mitra Makassar. 2) There is no direct positive and significant effect between promotion on the consumer credit marketing performance of PT BPR Hasa Mitra Makassar. 3) There is a direct positive and significant influence between people on the consumptive marketing performance of PT BPR Hasa Mitra Makassar. 4) There is a direct positive and significant influence between price, promotion and people on the consumptive marketing performance of PT BPR Hasa Mitra Makassar.